2020
DOI: 10.1126/sciadv.abd0952
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in biodiversity loss across China under multiple environmental stressors

Abstract: Biodiversity is essential for the maintenance of ecosystem health and delivery of the Sustainable Development Goals. However, the drivers of biodiversity loss and the spatial variation in their impacts are poorly understood. Here, we explore the spatial-temporal distributions of threatened and declining (“biodiversity-loss”) species and find that these species are affected by multiple stressors, with climate and human activities being the fundamental shaping forces. There has been large spatial variation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 57 publications
0
41
0
Order By: Relevance
“…This is another aspect of high CO 2 and stress combination that needs to be addressed, particularly in light of the potential negative effects of stress combinations on NUE. Because the breath of high CO 2 effects on crops is too vast to cover here, the reader is directed to several excellent reviews on the subject (Ainsworth and Long, 2021;Bright and Lund, 2021;Delabre et al, 2021;Green et al, 2020;Kurganskiy et al, 2021;Lamichaney and Maity, 2021;Lu et al, 2020;Penuelas et al, 2020;Schmidt et al, 2021;Smith, 2021;Soh et al, 2019;Tausz-Posch et al, 2020;Toreti et al, 2020;Wang and Liu, 2021;Wang et al, 2020;Xu et al, 2020).…”
Section: Stress Combination In a High Co 2 Environmentmentioning
confidence: 99%
“…This is another aspect of high CO 2 and stress combination that needs to be addressed, particularly in light of the potential negative effects of stress combinations on NUE. Because the breath of high CO 2 effects on crops is too vast to cover here, the reader is directed to several excellent reviews on the subject (Ainsworth and Long, 2021;Bright and Lund, 2021;Delabre et al, 2021;Green et al, 2020;Kurganskiy et al, 2021;Lamichaney and Maity, 2021;Lu et al, 2020;Penuelas et al, 2020;Schmidt et al, 2021;Smith, 2021;Soh et al, 2019;Tausz-Posch et al, 2020;Toreti et al, 2020;Wang and Liu, 2021;Wang et al, 2020;Xu et al, 2020).…”
Section: Stress Combination In a High Co 2 Environmentmentioning
confidence: 99%
“…Here, we present subfossil chironomid records from four lakes in the Southwest China. As a biodiversity hotspot (Myers et al 2000), the Southwest China possesses many lakes with different backgrounds of natural properties and human impacts, and some of them are faced with risks of continuous loss in biodiversity (Lu et al 2020). Previous studies related to diversity or regime shifts in this region were mainly focused on bacteria, phytoplankton, and plants (Wang et al 2016; Song et al 2019; Wang et al 2020).…”
Section: Figmentioning
confidence: 99%
“…While the roles of individual threats to biodiversity, including climate change, habitat loss, and pollution, are well documented, much less is known about how these drivers interact and how their interactions vary across locations. Through analysis of the spatial-temporal distributions of threatened and declining species across China, Lu et al (1) found that these "losing" species are affected by multiple stressors, with climate and human activities as the fundamental shaping forces. Expanding construction and intensifying pollution have led to habitat loss and degradation, threatening high proportions of amphibians, mammals, and reptiles.…”
Section: Multiple Stressors Drive Biodiversity Lossmentioning
confidence: 99%